1997
DOI: 10.1093/carcin/18.8.1679
|View full text |Cite
|
Sign up to set email alerts
|

Fasting during promotion, but not during initiation, enhances the growth of methylnitrosourea-induced mammary tumours

Abstract: The purpose of this work was to investigate the effect of fasting on the induction and growth of chemically-induced mammary carcinogenesis. Female Sprague-Dawley rats were given methylnitrosourea (MNU) i.p. (50 mg/kg) at 50 days of age; a group of rats were exposed to 4 day fasting followed by 1 day of refeeding before the administration of the carcinogen, while another group was exposed to three cycles of 3 days fasting in 10 days, beginning 1 week after MNU injection. Fasting enhanced the development of mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In female rats, 3 cycles of 3 days of fasting and 10 days of ad libitum feeding, started a week after initiation with methylnitrosourea intraperitoneally, increased multiplicity of mammary tumors [53]. Even a single 3-day period of fasting, imposed a week after initiation with dimethylbenz[a]anthracene, enhanced mammary tumor growth and reduced tumor latency [54].…”
Section: Fastingmentioning
confidence: 99%
“…In female rats, 3 cycles of 3 days of fasting and 10 days of ad libitum feeding, started a week after initiation with methylnitrosourea intraperitoneally, increased multiplicity of mammary tumors [53]. Even a single 3-day period of fasting, imposed a week after initiation with dimethylbenz[a]anthracene, enhanced mammary tumor growth and reduced tumor latency [54].…”
Section: Fastingmentioning
confidence: 99%
“…Nevertheless, the benefits and feasibility of such diets for human subjects have not been adequately identified and investigated. Interestingly, a recent study demonstrated that an IER diet modified the hypothalamic expression of critical genes that are involved in lipid metabolism, inflammation, and the regulation of the insulin and leptin pathways [14] Non-adherence is a common issue with human dietary interventions designed for weight loss, especially in diets that depend on restricted energy intake [15]. For instance, a systematic review and meta-analysis involving 45 randomized controlled trials that examined the effects of energy restriction interventions in obese individuals reported that nearly 28% of subjects dropped out due to non-adherence to their dietary interventions [16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a systematic review and meta-analysis involving 45 randomized controlled trials that examined the effects of energy restriction interventions in obese individuals reported that nearly 28% of subjects dropped out due to non-adherence to their dietary interventions [16]. Accordingly, increasing the ability to adhere to an IER diet is an important factor for its success [15,17]. One of the critical elements for adherence may be increased satiety.…”
Section: Introductionmentioning
confidence: 99%
“…[50] In another study of rats, three periods of fasting/refeeding following carcinogen administration increased mammary tumor number compared with rats either fed ad libitum or subjected to only one period of fasting/refeeding. [51] We speculate that the periods of refeeding at the time of high-level carcinogen administration may enhance tumor development due to the release of many growth factors as well as the hormonal milieu present in young rats as they become sexually mature. The relevance of this to the etiology of most human cancers is not known.…”
Section: Introductionmentioning
confidence: 99%